THE ANALYSIS OF FACTORS AFFECTING CONSUMER PURCHASE DECISIONS AT NUSANTARA SHOP KEPAHIANG REGENCY - Abdul Kohar; Neri Susanti; Nirta Vera Yustanti (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2020)
This study aims to analyze factors affecting theonderdile to purchase stores Nusantara kepahiang. This study is conducted by using rating scale and in depth kuisioner. The samples used in this study consist 60 people who come into the store consumers Nusantara Kepahiang clothing. The respondents were asked to give perception about factors affecting the decision to purchase clothing stores Nusantara kepahiang. Data obtained from 60 respondents that were processed by using rating scale analysis. ovrall,in this case can be seen calculasion of the rating scale which shows that average on indicators of the cultural factors of 1,232 and lies in the class agreed interval (1020-1260),indicators of the social factors of 1,222 and lies in the class agreed interval (1020-1260),indicators of the personal factors of 1,229 and lies in the class agreed interval (1020-1260),indicators of the psychological factors of 1,200 and lies in the class agreed interval (1020-1260). Mean that decision to buy the most dominant in the Nusantara Kepahiang is psychological factors, while purchasing decisions at 1,200 and lies in the interval class agreed. The results of the analysis is factors affecting the decision to purchase clothing stores Nusantara kepahiang.